Resveratrol enhances the tolerance of Malus hupehensis to potassium deficiency stress - Sun, Zhijuan; Wang, Tianchao; Li, Jianyu; Zheng, Xiaodong; Ge, Hongjuan; Sha, Guangli; Ma, Changqing; Zhao, Qiang; Wang, Caihong; Tian, Yike (Frontiers in Plant Science, 2024)
Potassium (K) deficiency in plants can lead to metabolic disorders and growth retardation. Currently, nearly 50% of the arable land in China is experiencing a K resource deficit, significantly hindering the development of the apple industry. Resveratrol (Res), a phytoalexin, has been extensively reported to enhance plant resistance against various abiotic stresses. However, there have been no reports on the response of Res to K+ deficiency stress in apples. This study aims to investigate the effect of exogenous Res on the K+ deficiency tolerance of Malus hupehensis. The results demonstrated that applying 50 μM of exogenous Res could enhance the tolerance of M. hupehensis to K+ deficiency stress. Compared to non-Res treatments, external application of Res alleviated leaf chlorosis and improved root growth in apple seedlings. Additionally, it increased antioxidant enzyme activity, thereby reducing the production of reactive oxygen species induced by K+ deficiency stress. Res also regulated proline and soluble sugar content to maintain osmotic balance. Moreover, Res helped maintain the balance of mineral element contents in apple seedlings and the normal K+: Na+ ratio by enhancing the influx of K+. Furthermore, exogenous Res regulated the expression of related kinase genes, promoting Ca2+ signal transduction in response to K+ deficiency stress and inducing the expression of K+ transport genes to enhance K+ absorption, thus supporting normal plant growth. In conclusion, this study provides a theoretical basis for the application of exogenous Res to alleviate K+ deficiency stress in apples.